Low weight, overweight, obesity and growth in adolescents in Peru (2009-2010). - Pajuelo R., Jaime (2015)
Introduction: Teenagers represent somehow a fifth of the population and are not away from nutritional problems. Objectives: To determine the nutritional status, growth and some determining factors in adolescents in Peru. Design: Descriptive, observational, transversal study. Participants: Adolescents. Interventions: Weight, height, body mass index were obtained from 14 753 adolescents 10-19 yearold. Must percentile reference and WHO Z score were used. Main outcome measures: Averages and DE, prevalence CI 95%, OR IC 95%, chi-square and multiple regressions were obtained. Results: Prevalence of deficit, underweight, normal, overweight and obesity found respectively were 2.6; 5.9; 79; 9.3 and 3.2 (Must); 0.2; 1.1; 82.6; 12.5; 3.5% (WHO). Overweight- obesity predominated in urban areas, in non-poor areas , the coast, jungle and Metropolitan Lima,and in those lived below 3 000 masl. Risk factors for deficitunderweight were: male gender, extremely poor, non-extremely poor, living in the northern coast and central sierra; and as protective factor living below 1 000 masl. Risk factors for overweight-obesity were living in urban areas, southern coast and below 1 000 masl, and living between 1 000 and 2 999 meters; and protective factors were being extremely poor, and not extremely poor, living in the northern coast, northern sierra, central sierra, southern sierra and in the jungle. Growth retardation was found in 28.5% of adolescents 10 to 17 years. Risk factors for growth retardation were living in rural areas, in most geographic domains except the southern coast, extreme and non-extreme poverty levels, altitude 1 000-2 999 and above 3 000 masl. Conclusions: Overweight-obesity was a problem of greater magnitude and confirmed its tendency to increase with time. Height attained was far from satisfactory and reflected maintenance of unsatisfied basic needs.